Nonconvulsive Status Epilepticus in Adults: Types, Pathophysiology, Epidemiology, Etiology, and Diagnosis - Rüegg, Stephan (Neurology International Open, 2017)
Nonconvulsive status epilepticus (NCSE) is defined by permanent electroclinical nonconvulsive epileptic activity or a series of nonconvulsive seizures without recovery to baseline. This “silent” manifestation of lasting neurological symptoms, like aphasia, confusion, etc., impedes easily recognizing NCSE. The most important diagnostic step often is to consider the possibility of NCSE. NCSE can only be confirmed by an immediate EEG recording. Epidemiological studies show slight preponderance of convulsive status epilepticus (CSE) over NCSE (60:40%); however, this might result from lack of recognition of NCSE because of its very unspectacular manifestation. Regarding pathophysiology, the neuronal mechanisms are identical for both NCSE and CSE, but they spare the primary motor neurons. Permanent hyperexcitability may damage the neurons involved in NCSE the same way as the motor neurons in CSE. However, NCSE is spared from the life-threatening secondary pathophysiological sequelae of CSE (lactic acidosis, respiratory exhaustion, rhabdomyolsis, etc.). Nevertheless, autonomic dysregulation (arrhythmias (ventricular tachycardia/asystolia), apneas) may also expose the patient to substantial acute risks. There are a myriad of causes for NCSE and they are mainly medication errors (insufficient adherence or addition of new drugs with interactions) in patients with known epilepsy. In these patients and in those without known epilepsy, other causes include metabolic, toxic, structural (tumors, hemorrhages, ischemia), infectious, inflammatory, and autoimmune causes. Thus, it is germane to extensively search for the cause of the NCSE because the immediate and proper therapy of the underlying cause of, especially the acute symptomatic, forms of NCSE is at least as important as the antiictal treatment.
Keywords: nonconvulsive status epilepticus; coma; encephalopathy behavioral changes; EEG